2008
DOI: 10.1002/jrs.2064
|View full text |Cite
|
Sign up to set email alerts
|

Barcoding bacterial cells: a SERS‐based methodology for pathogen identification

Abstract: A principal component analysis (PCA) based on the sign of the second derivative of the surface-enhanced Raman scattering (SERS) spectrum obtained on in situ grown Au-cluster-covered SiO 2 substrates results in improved reproducibility and enhanced specificity for bacterial diagnostics. The barcode-generated clustering results are systematically compared with those obtained from the corresponding spectral intensities, first derivatives and second derivatives for the SERS spectra of closely related cereus group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
154
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(158 citation statements)
references
References 38 publications
3
154
0
1
Order By: Relevance
“…Bacteria discrimination was first shown with Ag colloid SERS, showing discrimination at the strain level for E. Coli [319]. Differences in SERS spectra of various other bacteria species was also shown shortly after [320], and was shown to be potentially useful for bacteria 'barcoding' using multivariate statistics [321]. Different Ag NPs used for SERS were investigated for their antibacterial activity, and it was found that smaller (18 nm) were more toxic to bacteria than 80nm [322].…”
Section: Applicationsmentioning
confidence: 99%
“…Bacteria discrimination was first shown with Ag colloid SERS, showing discrimination at the strain level for E. Coli [319]. Differences in SERS spectra of various other bacteria species was also shown shortly after [320], and was shown to be potentially useful for bacteria 'barcoding' using multivariate statistics [321]. Different Ag NPs used for SERS were investigated for their antibacterial activity, and it was found that smaller (18 nm) were more toxic to bacteria than 80nm [322].…”
Section: Applicationsmentioning
confidence: 99%
“…Posteriormente, producto de la presencia de las bacterias y su interacción con el láser incidente, los pilares se alinean entre sí creando de este modo hot spots (zonas de aumento de campo electromagnético) que incrementan la intensidad de la señal Raman. Este mismo efecto ha sido utilizado para explicar el efecto SERS en otros estudios, utilizando sustratos diferentes [3,7,[16][17][18][19].…”
Section: Modos De Vibración Representativos De E Coliunclassified
“…The identification and classification of bacteria causing urinary tract infections were demonstrated by Goodacre group using citrate reduced AgNPs [123]. The use of gold-coated silica nanoparticles as substrate and a barcoding approach was later used for the bacterial identification by Zeigler group [144]. The major problem with the application of SERS as a technique for microorganism identification is the spectral reproducibility.…”
Section: Detection Identification and Characterization Of Biomacrommentioning
confidence: 99%